Analisis Nilai Entrance Skin Dose (ESD) dan Dosis Hamburan pada Area Tiroid dan Area Gonad pada Phantom PMMA Planar Menggunakan Pesawat Fluoroskopi C-Arm - Asmayati; Astuty, Sri Dewi; Prastowo, Alan Tanjung Aji; Dewang, Syamsir; Ibrahim, Ajeng Anggreny; Pratiwi, Ayu Hardianti (JFT : Jurnal Fisika dan Terapannya, 2025)
A study has been conducted analyzing the Entrance Skin Dose (ESD) value on PMMA phantoms based on variations in Field of View (FOV) and thickness. In addition, the magnitude of the dose scattering that reaches the thyroid and gonad areas of radiation workers when C-Arm fluoroscopy examination is performed was also tested. The variation in phantom thickness values ​​was 15, 20, and 25 cm while the variation in FOV irradiation values ​​was 12, 15, 17, and 20 cm. The purpose of the study was to determine the magnitude of the change in ESD value due to changes in object thickness which will also directly affect changes in peak voltage for each irradiation. This also has implications for providing an increasing scattering dose due to the presence of the object. The results showed that the larger the FOV and thickness of the phantom, the higher the ESD value received. At a phantom thickness of 25 cm, ESD increased from 6.42 mGy at a FOV of 12 cm to 11.61 mGy at a FOV of 17 cm. The scatter dose value that reaches the thyroid area is a maximum of 22.31 µSv at FOV 20 cm, while the gonad area receives 1.647 µSv, which is lower because the fluoroscopy machine is equipped with Pb protection for radiation workers when performing interventions. The conclusion in C-arm fluoroscopy examinations, radiation workers must also use protective equipment for other vital areas such as Pb glasses and neck protection to be safer from scattered radiation.